Claiming Your Own Identity and Positionality: The First Steps toward Establishing Equity and Social Justice in Science Education - Rodriguez, Alberto J. (2023)
If there is one major aspect that calls for science education reform in both Costa Rica and the United States have in common is that in both countries, science teachers are expected to establish an inclusive environment where students feel free to engage in discussions and investigations of real-world (socially relevant) issues. However, one aspect that teacher education programs in both countries have also in common is taking for granted the complexity of developing a teacher identity with the kind of cultural awareness, relevant pedagogy and content knowledge, and positionality necessary to meet the ambitious calls for science education reform. In our study, we sought to contribute to the understanding of these issues by assisting 17 pre-service high school science teachers in Costa Rica explore how their identity development and positionality might impact their abilities to establish culturally inclusive and socially relevant science classrooms. To this end, we offered participants culturally and socially relevant science teaching and curriculum development workshops for the last year and a half of their teacher professional program. Findings from the project’s first phase of analysis indicate significant growth in the participants’ identity development as culturally inclusive teachers responsible for making the science curriculum relevant for everyone.